Statement by the Managing Director on the Independent Evaluation Office Report on the IMF Advice on Unconventional Monetary Policies. (Policy Papers; Policy Paper ;, 2019)
I welcome the report of the Independent Evaluation Office (IEO) on the IMF Advice on Unconventional Monetary Policies (UMP). The report recognizes that the Fund's engagement on UMP since the Global Financial Crisis has been wide-ranging and, in many respects, impressive. The report offers valuable insights on how to further improve the timeliness and value added of the IMF's advice on UMP. Accordingly, I broadly support the general thrust of IEO's recommendations, which are helpful in informing Management's consideration of how to push forward the Fund's work in this area.